2008
DOI: 10.1021/jm800194k
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Bis-indole Derivatives

Abstract: This paper reports the synthesis of compounds formed by two indole systems separated by a heterocycle (pyridine or piperazine). As a primary screening, the new compounds were submitted to the National Cancer Institute for evaluation of antitumor activity in the human cell line screen. The pyridine derivatives were far more active than the piperazine derivatives. For the study of the mechanism of action, the most active compounds were subjected to COMPARE analysis and to further biological tests including prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 34 publications
(86 reference statements)
1
53
0
Order By: Relevance
“…All spectral data were in accordance with assumed structures. The trans conformation of these derivatives were confirmed by a reference 3 J HH value of 16 Hz obtained for the HC]CH group of (E)-3-(6-fluoro-1H-indol-3-yl)acrylic acid [33].…”
Section: Resultssupporting
confidence: 53%
“…All spectral data were in accordance with assumed structures. The trans conformation of these derivatives were confirmed by a reference 3 J HH value of 16 Hz obtained for the HC]CH group of (E)-3-(6-fluoro-1H-indol-3-yl)acrylic acid [33].…”
Section: Resultssupporting
confidence: 53%
“…46 In this present study, it has been shown that bisindole conjugate 5b exhibited profound control over growth factor signaling pathway mediated by PI3K/ AKT/mTOR and modulate the balance between survival signals as well as apoptotic signals via SIRT and p53 axis in breast cancer cell-lines. Till date not many SIRT inhibitors have been studied in metabolic disorders, nor their regulation of balance between growth factor signaling and p53 mediated apoptotic pathway in breast cancer cells is understood.…”
Section: Discussionmentioning
confidence: 55%
“…Pharmacological studies of indolic compounds reported a wide variety of important biological properties such as anti-inflammatory [2,3], analgesic [3], antibacterial [4], antifungal [5], neuroprotective [6,7], antitumour [8][9][10] and antioxidant properties [11].…”
Section: Introductionmentioning
confidence: 99%